Characterization of Physiological Biomarkers in Long-Term Kratom (Mitragyna speciosa Korth.) Users: A Preliminary Study - Wanumaidah Saengmolee (Prince of Songkla University, 2023)
Doctor of Philosophy (Physiology), 2022